Chirality-activated mechanoluminescence from aggregation-induced emission enantiomers with high contrast mechanochromism and force-induced delayed fluorescence. (1st July 2019) - Chen, Yitong; Xu, Chao; Xu, Bingjia; Mao, Zhu; Li, Jian-An; Yang, Zhan; Peethani, Naga Raju; Liu, Cong; Shi, Guang; Gu, Feng Long; Zhang, Yi; Chi, Zhenguo
Abstract : A pair of AIE enantiomers exhibit chirality-activated mechanoluminescence and circularly polarized luminescence, as well as force-induced multiple-variations in emission properties. Abstract : A pair of chiral aggregation-induced emission (AIE) enantiomers and their racemate exhibit not only distinctively different circularly polarized luminescence behaviors, but also completely opposite mechanoluminescence (ML) activities. The data from single crystal analysis identifies that the bright ML of the AIE enantiomers is probably activated by their molecular chirality, which enables unique chiral crystal structures with a polar space group and compact molecular packing. These experimental findings provide a direction for harvesting prominent ML from AIE luminogens. Concurrently, high contrast mechanochromism with larger Δ λ PL, max and Δ Φ F, s values by up to 140 nm and 0.61 respectively have been achieved from this AIE system, which represents the state-of-the-art mechanochromic performance for ML emitters. Moreover, force-induced white-light emission and thermally activated delayed fluorescence have also been observed. The results of theoretical calculations suggest that the destruction of intermolecular interactions and conversion of molecular conformation account for the significant multiple-variations in emission properties triggered by a single mechanical stimulus.